An examination of soil and water conservation practices in the paddy fields of Guilan province, Iran - ASHOORI,DARYOUSH (2016)
ABSTRACT This study examined the use of soil and water conservation (SWC) practices among rice farmers in Iran. A random sample of 400 rice paddy farmers in the Foumanat plain of Guilan province, who use SWC measures, was drawn from a population of 52 thousand farmers. A two-part questionnaire was used to examine the level of utilization of SWC practices and to profile paddy farmers. Internal consistency was demonstrated with a coefficient alpha of 0.76, and the content and face validity of the instrument was confirmed by a panel of soil and water experts. Descriptive and analytical statistics were used to analyze the data. Results of ANOVA indicated that the mean levels of SWC practices vary considerably at the 0.01 level of significance by groups of age, education, non-agricultural income, production costs, yield, cultivated paddies and distance from home to the farm or to the main road. Similarly, significant differences were observed by groups of family size, rice production, ownership of livestock and profits from rice production at 0.05 level. The levels of experience in agriculture and ownership of poultry were found to have no significant effects on SWC practices.